Justification of the choice of demulsifier and technology for effective emulsion destruction in the borehole production collection system - Yusupova Liliya; Almukhametova Elvira; Amelchenko David (E3S Web of Conferences)
The presented work examines the causes of the formation of petroleum emulsions, their classification and properties. An overview of methods for combating water-oil emulsions is given. The characteristics of demulsifier brands, such as purpose, appearance, kinematic viscosity and pour point, have been studied. The characteristics of the field oil, gas and water collection system are described, as well as a diagram of a booster pumping station and its specific reagent injection site. The characteristics influencing the destruction of oil emulsions by means of a demulsifier are discussed. The article presents the selection and analysis of the studied demulsifiers. The qualitative state of the interphase boundary, the content of residual water and the ability to destroy the emulsion are investigated. The calculation of the operating flow rate and dosage of the most cost-effective demulsifier, as well as the supply of a dosing pump, is given.